2008
DOI: 10.1002/eji.200838143
|View full text |Cite
|
Sign up to set email alerts
|

Regulatory T cells and immune computation

Abstract: The role of Treg in immune regulation is the topic of this Viewpoint series in the European Journal of Immunology (EJI); the question to be discussed in this section is the effector function of Treg in immune regulation. In this manuscript, we take on the following three postulates outlined by Rolf Zinkernagel on the role of Treg in the control of immunity. First, the immune response is regulated primarily by the antigen and not by Treg. Second, immune non‐responsiveness results from the deletion of specific r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0
1

Year Published

2008
2008
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 37 publications
0
6
0
1
Order By: Relevance
“…It is known that the maturation status of DCs is crucial for the initiation of primary immune responses, and recently, it was confirmed that immature DCs are prone to induce regulatory T cells, which are a key components in maintaining immune homoeostasis and regulating immune responses in helminth infections (10–13). Although regulatory T cells were first described as differentiating in newborn thymus, it is now clear that they also develop in the periphery from nonregulatory T cells in a process termed ‘conversion’ (14). Some observations suggest that induction of regulatory T cells occurs during infections with certain pathogens, including Bordetella pertussis (15), the nematode Onchocerca volvulus (16), and schistosome infection.…”
Section: Introductionmentioning
confidence: 99%
“…It is known that the maturation status of DCs is crucial for the initiation of primary immune responses, and recently, it was confirmed that immature DCs are prone to induce regulatory T cells, which are a key components in maintaining immune homoeostasis and regulating immune responses in helminth infections (10–13). Although regulatory T cells were first described as differentiating in newborn thymus, it is now clear that they also develop in the periphery from nonregulatory T cells in a process termed ‘conversion’ (14). Some observations suggest that induction of regulatory T cells occurs during infections with certain pathogens, including Bordetella pertussis (15), the nematode Onchocerca volvulus (16), and schistosome infection.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, many genes involved in immune regulation possess multiple dioxin response elements [DREs] in their promoter region. (10, 11) Studies performed in AhR −/− mice have shown an enhanced inflammatory response to cigarette smoke or endotoxin, with elevated levels of tumor necrosis factor-α [TNFα] and interleukin-6 [IL-6]. (12, 13) AhR is essential in the regulation of cell cycle, lipid metabolism (14) circadian rhythm (15) and immune response.…”
Section: Introductionmentioning
confidence: 99%
“…3 Two major populations of Tregs, with complementary and overlapping functions in the control of immune response in vivo, exist, as follows: natural (or constitutive) and inducible (or adaptive) Tregs. Numerous studies have demonstrated the therapeutic use of Ag-specific Tregs in various experimental models of autoimmune diseases and allogeneic transplantation, providing long-term tolerance by active and specific regulation of self-Ag and alloantigenspecific T cells (3)(4)(5). These findings have opened up exciting opportunities for new therapies in several human diseases that are associated with Treg dysfunction.…”
mentioning
confidence: 99%